2020
DOI: 10.13031/aea.13368
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Three DifferentSpades for Residual Plastic Film Recycling Machine

Abstract: HighlightsEffectively separating the “white pollution” from agricultural soil.Three different spades for mechanical recycling residual film were tested.All spades had a similar draft requirement and soil disturbance trend.Spade A provided a higher residual film recovery rate.Abstract. Plastic film mulching cultivation provides important support for increasing the crop yield and ensuring food security, but residual plastic film pollution has become a prominent problem affecting the sustainable development of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Bringing Equation (31) into Equation ( 21), it can be seen that when λ takes 1, L 1 ≤ 0.317 m. Therefore, the maximum spacing (L 1 ) between two adjacent pickup nail teeth can be 285.75 mm. At this point, the tensile force received by the plastic film is less than its longitudinal breaking force, meeting the operational requirements of the picking device.…”
Section: Force Analysis Of Residual Filmmentioning
confidence: 99%
See 2 more Smart Citations
“…Bringing Equation (31) into Equation ( 21), it can be seen that when λ takes 1, L 1 ≤ 0.317 m. Therefore, the maximum spacing (L 1 ) between two adjacent pickup nail teeth can be 285.75 mm. At this point, the tensile force received by the plastic film is less than its longitudinal breaking force, meeting the operational requirements of the picking device.…”
Section: Force Analysis Of Residual Filmmentioning
confidence: 99%
“…At this time, the residual film could not be picked up. After the operation of the machine, there was a hole mark on the residual film, but the residual film was still attached to the soil [31].…”
Section: Force Analysis Of Residual Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…The particle trajectory is shown in Figure 8a, so the lower limit of wind speed is 14.5 m/s. It may be determined that there is air-assisted film-stripping at the particle inlet by selecting the middle horizontal section of the fluid domain as the study object and analyzing the velocity distribution of the airflow field, as shown in Figure 8b,c [25]. The standard k-ε model and the standard wall function method are used to calculate the flow field, and the DPM is used to calculate the particle motion.…”
Section: Numerical Computation Of Dpmmentioning
confidence: 99%
“…Compared with planting cotton in open fields, planting cotton with film mulching cultivation can increase the production by 30~50% in general and 40~60% at most. According to statistics, mulch film could be detained for 8~10 years in the soil, and the average residue quantity of waste film reaches 187.5 kg per hectare, which causes the production to reduce by 17% [4][5][6][7][8][9][10][11][12]. The looser the soil is, the lower the moisture content and viscosity are, and the higher the plastic film pick-up rate is.…”
Section: Introductionmentioning
confidence: 99%